ANALISIS MODAL KERJA UNTUK MENINGKATKAN PROFITABILITAS PADA PT PSIKOLOGI BAGI BANGSA PERIODE 2012-2016 - HASBI BASITH SUKARNO; SILVI ARIESTY ZULKHAIDAH (EKBIS (Ekonomi & Bisnis), 2018)
This research has a purpose to analyze the work modality to increase profitability on PT Psikologi Bagi Bangsa in 2012-2016 period.The research method has been used is descriptive research method with quantitative approach. Data analysis techniques is used here are normality test, correlation coefficient, coefficient of determination, simple linear regression analysis and t-test. Methods of data collection used by means of observation, interviews, literature review, and websites that have a close relevance to the subject matter.From the conducted research, the rise and fall of profit gained is influenced by the amount (up or down) of working capital owned. It was proved by the results of the correlation test showed 0.957, meaning that the two variables in the test have a very close relationship. And obtained by result of linear regression analysis Y = 19260237,545 + 0,105X.The suggestion given by the researcher is the financial staff should be wiser in using the available working capital and more thoroughly in allocating these funds, in order to be used as much as possible to get the maximum profit also for PT Psikologi Bagi Bangsa and anticipate that no use of funds derived from debt to avoid interest expense.